Discrimination and Workers' Expectations - Antonio Filippin (Institute for the Study of Labor (IZA), 2003)
The paper explores the role of workers? expectations as an original explanation for the puzzling long run persistence of observed discrimination against some minorities in the labor market. A game of incomplete information is presented, showing that ex ante identical groups of workers may be characterized by unequal outcomes in equilibrium due to their different beliefs, even though discriminatory tastes and statistical discrimination by employers have disappeared. Wrong beliefs of being discriminated against are self-confirming in this circumstance, being the ultimate cause of a lower percentage of promotions which supports these wrong beliefs.
Keywords: D84; J24; C79; J15; J71; 330; discrimination; workers? expectations; self-confirming beliefs; Arbeitsmarktdiskriminierung; Ethnische Diskriminierung; Dynamisches Spiel; Unvollkommene Information; Arbeitsproduktivität; Erwartungstheorie; Theorie